HELICOBACTER PYLORI VACA, CAGA, ICEA1, AND ICEA2 GENOTYPES IN GASTROINTESTINAL DISEASES PATIENTS FROM MOSUL/IRAQ - Abdul-Ghani Muhammad, Muhammad; Ahmed Abdullah, Basima; Ahmed Altaie, Anmar (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Helicobacter pylori is a key cause of gastroduodenal disorders, with cagA-positive strains linked to gastric cancer primarily in Western populations. Other virulent genes may enhance the effects of cagA in disease development. This study sought to identify common H. pylori virulence genes in patients with gastrointestinal disorders. Methods: Biopsy specimens were collected from 100 patients. All DNA samples underwent PCR to confirm H. pylori infection, with positive samples further genotyped. Each PCR reaction used specific primers. Results: EGD findings indicated abnormalities in 89% of patients and normal results in 11%. The gene detection rate was 77%. Analysis of 77 samples showed virulence gene prevalence as 40.3% for cagA, 46.8% for iceA1, and 31.2% for iceA2, with 76.6% containing vacA. The vacA gene was the most common, except in normal findings, where iceA1 was second, followed by cagA and iceA2. High vacA positivity was noted across various conditions, while cagA and iceA2 were absent in some patient groups. A 100% positivity rate for iceA1 was observed in patients with combined gastritis and gastric ulcers. The combination of cagA, iceA1, and vacA was observed in 20.8% of cases, while vacA and iceA1 appeared in 18.2% and vacA and iceA2 in 14.3%. Furthermore, the combination of cagA, iceA2, and vacA was found in 9.1% of cases. Conversely, the combined genotypes of cagA with iceA1, iceA2, and vacA were present at lower frequencies of 2.6%, 3.9%, and 3.9%, respectively. The individual occurrence of virulence factors varied, with vacA present in 10.4% of cases, iceA1 in 5.2%, and iceA2 in 3.9%. Additionally, cagA, iceA1, iceA2, and vacA genes were absent in 7.8% of cases. Novelty: This study reveals unique H. pylori virulence gene combinations and prevalence in Mosul, Iraq, offering regional-specific insights.